KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU (Studi Kasus Pada Guru PNS SMA Negeri Se-Kota Tegal) - Daryono, 14.5202.0099; Sutomo, Y. (Jurnal Mahasiswa Pasca Sarjana, 2016)
The purpose of this study was to analyze the influence of professional competence, motivation, leadership principals on teacher performance and analyze the impact of school leadership in moderating the influence of professional competence and motivation to work on the performance of government school teachers in SMA as the city of Tegal. The object of this study was the entire government school teachers in SMA as the city of Tegal. This research uses a quantitative research with a sample of 153 teachers. The analytical method used in this research is multiple linear regression. The method of collecting data in this study using a questionnaire with proportional randomsampling technique and formula Slovin.Keywords: Leadership, Professional Competence, Motivation, Performance